High school English teachers’ perceptions and use of motivational strategies in EFL classes : - Trần, Thì Mỵ (Trường Đại học Cần Thơ, 2018)
The study attempts to examine as to how the high school English teachers perceived and used the motivational strategies in the EFL classes. The main purpose of the study is to find out the motivational strategies used by the high school teachers in their classes and to figure out their challenges when implementing motivational strategies in EFL classes.